Health Impact Assessment of the 2020 Washington State Wildfire Smoke Episode: Excess Health Burden Attributable to Increased PM2.5 Exposures and Potential Exposure Reductions. (6th May 2021) - Liu, Yisi; Austin, Elena; Xiang, Jianbang; Gould, Tim; Larson, Tim; Seto, Edmund
Abstract: Major wildfires starting in the summer of 2020 along the west coast of the United States made PM2.5 concentrations in this region rank among the highest in the world. Washington was impacted both by active wildfires in the state and aged wood smoke transported from fires in Oregon and California. This study aims to estimate the magnitude and disproportionate spatial impacts of increased PM2.5 concentrations attributable to these wildfires on population health. Daily PM2.5 concentrations for each county before and during the 2020 Washington wildfire episode (September 7–19) were obtained from regulatory air monitors. Utilizing previously established concentration‐response function (CRF) of PM2.5 (CRF of total PM2.5 ) and odds ratio (OR) of wildfire smoke days (OR of wildfire smoke days) for mortality, we estimated excess mortality attributable to the increased PM2.5 concentrations in Washington. On average, daily PM2.5 concentrations increased 97.1 μg/m 3 during the wildfire smoke episode. With CRF of total PM2.5, the 13‐day exposure to wildfire smoke was estimated to lead to 92.2 (95% CI: 0.0, 178.7) more all‐cause mortality cases; with OR of wildfire smoke days, 38.4 (95% CI: 0.0, 93.3) increased all‐cause mortality cases and 15.1 (95% CI: 0.0, 27.9) increased respiratory mortality cases were attributable to the wildfire smoke episode. The potential impact of avoiding elevated PM2.5 exposures during wildfire events significantly reduced the mortality burden. Because wildfire smoke episodes are likely to impact the Pacific Northwest in future years, continued preparedness and mitigations to reduce exposures to wildfire smoke are necessary to avoid excess health burden. Key Points: Elevated PM2.5 levels from a wildfire smoke episode were estimated to place a heavy mortality burden on counties in western Washington Counties in central and eastern Washington were estimated to have the highest per‐capita mortality during the wildfire smoke episode Reducing 40% of PM2.5 exposure for people below the federal poverty level was associated with 4.1 (95% CI: 0.0, 8.2) reduced all‐cause deaths